A simple model potential for hollow nanospheres - Köksal, K.; Öncan, M.; Gönül, B.; Gönül, B. (Condensed Matter Physics, 2014)
A new model potential is introduced to describe the hollow nanospheres like fullerene and molecular structures and to obtain their electronic properties. A closed analytical solution of the corresponding treatment is given within the frame of supersymmetric perturbation theory.